(untitled) (Research, Society and Development, 2021)
Fertilization is the act of adding fertilizers to the soil in order to provide essential nutrients for the development of cultivated plants. However, the use of bovine manure can act as a source of weed propagules, including non-native species. Due to the importance and lack of research on the topic, the objective of the present study was to evaluate the seed bank present in bovine manure used by farmers in the municipality of Itabaiana, SE. For that, samples of bovine manure were collected in 10 rural properties in the municipality of Itabaiana, SE. The evaluation of the seed bank was carried out by accounting for emerged seedlings. Usual phytosociological indices were calculated for each species. Altogether 35 species were sampled, of which 28 native and seven non-native. The native species with the highest importance value was Euphorbia hirta, as it has the highest density (AD = 1122 ind.m-²) and is present in 28 sample units. The non-native species with the highest importance value was Eleusine indica, because it has the third highest density (AD = 171.2 m²) and is present in 21 sample units. The obtained results reveal that bovine manure has a high number of weed, which is quite worrying, as they are species that generate important environmental and economic impacts.